Size, composition and thermal induced band gap changing of nanostructured semiconductors - Nay Myo Tun (2010)
A nanostructure semiconductor can be divided into three groups such as group-IV from elemental, III-V and II-VI from compound materials. The band gap energy changes effectively if a function of temperature changes because the crystal lattice expansion and the inter-atomic bonds are weakened. A weaker bond means it only needs less energy to break the bond and take the electron in the conduction band. Temperature is one of the key elements in parameter settings to learn analysis of thermal activated process such as liquidation, evaporation, phase transition and crystal growth. In a four-parameter expression model, other fitting parameters involve such as fractional exponent, coefficient of thermal expansion, phonon temperature, debye temperature and degree of phonon dispersion ratio. Degree of phonon dispersion ratio can be divided into three categories like large dispersion, small dispersion and intermediate dispersion. A large dispersion is for Varshni’s formula model and a small dispersion is for Bose-Einstein-related model. Both models are approximation methods. An intermediate dispersion is for four-parameter expression model which is capable to produce adequate outcomes.